2001
DOI: 10.1006/aama.2001.0743
|View full text |Cite
|
Sign up to set email alerts
|

Integer Zeros ofq-Krawtchouk Polynomials in Classical Combinatorics

Abstract: dedicated to dominique foata on the occasion of his 65th birthdayInteger zeros of binary Krawtchouk polynomials occur in various problems of classical combinatorics. We present some of these properties and generalise them to q-Krawtchouk polynomials. We also give a survey of what is known about these zeros.  2001 Elsevier Science

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Krawtchouk polynomials and their generalisation appear in many areas of mathematics, see 2 [8]: harmonic analysis [11,6,17], statistics [7], combinatorics and coding theory [5,9,10,12,14], probability theory [8], representation theory (e.g., of quantum groups) [1,3,13], difference equations [2], and pattern recognition [15]. However, our motivation in this article was primarily driven by generalising the results obtained in [16] -and thus shedding more light on the qualitative structure of (generalisations of) Krawtchouk polynomials -and not yet with a specific application in mind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krawtchouk polynomials and their generalisation appear in many areas of mathematics, see 2 [8]: harmonic analysis [11,6,17], statistics [7], combinatorics and coding theory [5,9,10,12,14], probability theory [8], representation theory (e.g., of quantum groups) [1,3,13], difference equations [2], and pattern recognition [15]. However, our motivation in this article was primarily driven by generalising the results obtained in [16] -and thus shedding more light on the qualitative structure of (generalisations of) Krawtchouk polynomials -and not yet with a specific application in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Other generalizations of binary Krawtchouk polynomials have also been considered. [9] generalized some properties of binary Krawtchouk polynomials to q-Krawtchouk polynomials. [1] derived orthogonality relations for quantum and q-Krawtchouk polynomials and showed that affine q-Krawtchouk polynomials are dual to quantum q-Krawtchouk polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…for y ≈ Y − (z), p < z < 1 and unknown functions A (9) (z), B (9) (z). Using (87) in (97) we have, as β → ∞…”
Section: The Upper Part P < Z < 1 (Region Ix)mentioning
confidence: 99%
“…Lloyd's theorem [23] states that if a perfect code exists in the Hamming metric, then the Krawtchouk polynomial must have integral zeros [3], [5], [20]. Not surprisingly, these zeros have been the subject of extensive research [4], [7] [9], [10], [11], [16], [35].…”
Section: Introductionmentioning
confidence: 99%
“…Tèloc ta orjog¸nia q-polu¸numa kai oi rÐzec touc emfanÐzontai sthn sunduastik anlush kai sth jewrÐa kwdikopoÐhshc [11,18,43].…”
Section: Efarmogèc Twn Orjogwnðwn Poluwnômwnmentioning
confidence: 99%